PHOSPHO1 Suppresses Ferroptosis in Retinal Pigment Epithelial Cells by Reducing the Levels of Phosphatidylethanolamine Molecular Species - Zhiyang Chen; Xiaoman Zhu; Michael Mingze Lu; Qingjian Ou; Xueying Wang; Zhenzhen Zhao; Qi Shen; Qian Wang; Zhe Wang; Jing‐Ying Xu; Caixia Jin; Furong Gao; et al. (Advanced Science)
Abstract Iron‐induced lipid peroxidation of phosphatidylethanolamine (PE) species is a key driver of ferroptosis in retinal pigment epithelial (RPE) cells, a process closely associated with age‐related macular degeneration (AMD). The previous studies have demonstrated that induced retinal pigment epithelial (iRPE) cells generated by transcription factor‐mediated reprogramming exhibit superior therapeutic efficacy in treating AMD. In this study, it is found that these iRPE cells are resistant to ferroptosis and further identified phosphoethanolamine/phosphocholine phosphatase 1 (PHOSPHO1) as a critical regulator underlying ferroptosis resistance. Mechanistically, PHOSPHO1 inhibits ferroptosis through two distinct mechanisms. First, it reduces PE levels in the endoplasmic reticulum, thereby limiting PE‐derived lipid peroxidation. Second, it suppresses autophagy and ferritinophagy, leading to a reduction in intracellular free iron accumulation. Experiments using an in vivo rat model confirm that PHOSPHO1 effectively protects RPE cells from ferroptotic damage. These findings highlight PHOSPHO1 as a potential therapeutic target for AMD, providing insights into novel ferroptosis‐based intervention strategies.